A role of asynchrony of seasons in explaining genetic differentiation in a Neotropical toad - Thomé, Maria Tereza C. [UNESP]; Carstens, Bryan C.; Rodrigues, Miguel Trefaut; Galetti Jr, Pedro Manoel; Alexandrino, João; Haddad, Célio F. B. [UNESP] (Springer Nature, 2021)
The process of diversification can be studied at the phylogeographic level by attempting to identify the environmental features that promote and maintain population divergence. Here we investigate diversification in Rhinella granulosa, a Neotropical toad from northeastern Brazil, by testing a range of hypotheses that encompass different putative mechanisms reducing gene flow among populations. We sequenced single nucleotide polymorphisms and examined individual predictions related to the role of geographic barriers (rivers), ecological gradients, historical habitat stability, and spatial variation in climate seasonality, also known as the asynchrony of seasons hypothesis. This hypothesis postulates that temporal asynchrony of wet and dry seasons over short distances causes parapatric populations to become isolated by time. After determining genetic structure, inferring past distributions, ranking demographic models, and estimating the power of monthly climatic variables, our results identified two populations that are not associated with geographic barriers, biome gradients, or historical refugia. Instead, they are predicted by spatial variation in monthly rainfall and minimum temperature, consistent with the asynchrony of seasons hypothesis, supported also by our comparative framework using multiple matrix regression and linear mixed effects modeling. Due to the toad’s life history, climate likely mediates gene flow directly, with genetic differentiation being provoked by neutral mechanisms related to climate driven population isolation, and/or by natural selection against migrants from populations with different breeding times. The asynchrony of seasons hypothesis is seldom considered in phylogeographic studies, but our results indicate that it should be tested in systems where breeding is tightly coupled with climate.